PEMAKNAAN DAN MOTIF PESERTA VIRTUAL BLIND DATE DALAM RUANG KOMUNIKASI VIRTUAL @VIRTUALBLINDDATE (The Commercium, 2022)
This research aims to determine the meaning and motives of virtual blind date participants in the @virtualblinddate virtual communication room. By using the communication perspective and phenomenology theory of Alfred Schutz, this research analyzes participants' experiences when they participated in virtual blind date. As descriptive qualitative research with phenomenological methods, this research used Constructivism Paradigm, which sees social conditions as a systematics analysis. Data collection was obtained from the results of in-depth interviews with several participants according to the criteria of the informants. The result indicates the background of the participant's participation in the virtual blind date is grouped into two, namely the purpose motive (in order to) can be named as the main motive, and the cause motive (because of) can be named as supporting motives. The virtual blind date happened in a virtual room, whereas the meetings and interactions between participants occur directly using the device and were anonymous. Some of the meanings formed by participants after participating in virtual blind date activities are virtual blind date as a medium to find a partner, virtual blind date as a medium to find friends, virtual blind date as a medium for building relationships, and virtual blind date as a medium to increase experience. Keywords: Meaning, Motive, Virtual Blind Date, Phenomenology